The natural rate of interest and secular stagnation - Guido Baldi; Patrick Harms (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
In many advanced economies, there has been a declining trend in interest rates over the past thirty years. Since the financial crisis, interest rates have remained particularly low. Though a decrease in inflation explains part of the fall in nominal interest rates, there is also a clear downtrend in real interest rates. Against this backdrop, a debate has emerged over the factors that might have contributed to this decline. Potential persistent factors discussed under the heading of "secular stagnation" include a decline in profitable investment opportunities and high global savings rates. It is often argued that, due to these factors, the so-called natural interest rate, which is the level of interest rate consistent with stable, non-inflationary growth, has decreased. However, there are also arguments that the low interest rates are transitory and are due to factors such as post-crisis private debt deleveraging, a temporary "savings glut", or higher regulatory burdens for firms and households. This report summarizes the discussion on the underlying causes of the low interest rate environment and the potential for a period of secular stagnation.
Keywords: 330